Epidemiology study of Diarrhoea, Cholera, Typhoid, Hepatitis A and Hepatitis E in Middle East and North Africa Region - El Morabet, Rachida; Khan, Roohul Abad; Alsubih, Majed; Khan, Nadeem Ahmad; Yusuf, Mohammad; Khan, Parvez; Hrynzovskyi, Anatolii; Каlashchenko Svitlana; Lutsak, Olena (Ecological Questions, 2023)
Middle eastern countries are among one of the highly water stressed region in the world. Which renders it highly susceptible to water borne diseases. Water borne diseases epidemiology in Middle eastern countries were investigated in this research to determine existing health security in Middle eastern countries. Recent conflicts in the region, deteriorating water supply and infrastructure has led to major outbreaks of diarrhoea and cholera in Syria, Iraq, and Yemen. The water borne disease investigated are; diarrhoea, cholera, hepatitis A, hepatitis E and typhoid to present an overall scenario in the region. Despite proper infrastructure and water supply, stability (social, political and economy) of each country is vital to contain and curb water borne diseases and its outbreak in Middle eastern countries. According to the research results, it can be assumed that there is a high need for an elaborate study to come up with a comprehensive plan to mitigate and control water borne diseases in Middle eastern countries in terms of present and future perspective.